Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Fore Coffee (Studi Kasus pada Konsumen Fore Coffee di Kecamatan Medan Selayang) - Rayva Zalianti; Amrin Mulia Utama Nasution (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine and analyze: (1) the effect of service quality on customer loyalty; (2) the effect of customer satisfaction on customer loyalty; (3) the effect of service quality and customer satisfaction on customer loyalty. The population in this study are consumers residing in Medan Selayang District. Data was collected through questionnaires distributed to a sample of 96 respondents, namely Fore Coffee consumers. The sampling technique used was non-probability sampling, namely purposive sampling. The data analysis technique used Multiple Linear Regression Analysis, preceded by validity and reliability tests as well as classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. From the results of multiple linear regression analysis, the value obtained is Y= 12.844 + 0.185X1 + 0.450X2 + e. The results of the partial testing of hypothesis (1) show that there is no positive and significant effect between service quality and customer loyalty with a t-value < t-table (1.456 < 1.661) and significance > 0.05 (0.149 > 0.05). The results of testing hypothesis (2) show a positive and significant effect between customer satisfaction and customer loyalty with a t-value > t-table (3.361 > 1.661) and a significance value < 0.05 (0.001 < 0.05). In the simultaneous testing of hypothesis (3), there is a positive and significant effect of service quality and customer satisfaction on customer loyalty with a value of Fcount > Ftable (26.218 > 3.09) and a significance value < 0.05 (<0.001 < 0.05). The results of the coefficient of determination (R2) test were 0.361 or 36.1%, with the remaining 63.9% influenced by other variables outside the scope of this study.